Failure of the bovine papillomavirus to transform mouse embryo fibroblasts with a targeted disruption of the insulin-like growth factor I receptor genes. - Morrione, A (1995)
Mouse embryo cells with a targeted disruption of the insulin-like growth factor I receptor (IGF-IR) genes (R- cells) are refractory to transformation by the simian virus 40 large T antigen and/or an activated and overexpressed Ras, both of which readily transform cells from wild-type littermate embryos and other 3T3-like cells. R- cells are also refractory to transformation induced by overexpressed epidermal growth factor receptor and platelet-derived growth factor receptor beta. Since the platelet-derived growth factor receptor beta is required for transformation by bovine papillomavirus, we inquired whether the IGF-IR was also required for transformation by bovine papillomavirus E5 oncoprotein. We show here that R- cells are refractory to transformation by E5; reintroduction into R- cells of a human IGF-IR restores the susceptibility to transformation.